THE STRUCTURE OF TUBERCULOSIS IN ELDERLY AND SENILE PEOPLE IN THE ANDIJAN REGION - Maksumova D. K. (Scholars Digest Publishing, 2024)
Currently, the epidemic situation of tuberculosis in Uzbekistan has stabilized, but there is a tendency for tuberculosis to "age", i.e. it has become more common in the elderly. As of January 1, 2024, the number of people over the age of 60 in Uzbekistan amounted to about 3.5 million people, which is 9.4% of the total permanent population of Uzbekistan. In Uzbekistan, as in the whole world, there is an increase in the number of elderly and senile people. With age, the risk of infectious diseases, including tuberculosis, increases significantly due to a decrease in immunity and the presence of concomitant diseases (diabetes, cardiovascular diseases, etc.). In older people, the immune system is weakened, which makes them more susceptible to infections, including tuberculosis.